Health and economic impact of hepatitis B vaccination in the national immunization program in Belarus, Georgia, Kyrgyzstan, Republic of Moldova, Turkmenistan and Uzbekistan—a modelling study - Sadeghimehr, Maryam; Mosina, Liudmila; Sim, So Yoon; Datta, Siddhartha Sankar (Frontiers in Public Health, 2025)
Hepatitis B (HBV) remains a major public health concern in the WHO European Region, causing approximately 32,000 deaths annually as of 2022. Fortunately, HBV vaccination is highly effective in preventing infection. The WHO Regional Office for Europe established criteria for countries to be validated in reaching interim targets for HBV control through immunization, advancing toward the goal of hepatitis elimination. Belarus, Georgia, Kyrgyzstan, Moldova, Turkmenistan, and Uzbekistan conducted national HBV serosurveys, which revealed a significant reduction in chronic HBV prevalence among individuals born after the introduction of universal HBV vaccination in their national immunization programs. We analyzed these serosurvey data and developed a mathematical model to estimate the impact of various vaccination scenarios on HBV-related deaths and severe liver disease. The vaccination scenarios included the current vaccination strategies, as well as two other full-vaccination scenarios—one beginning at vaccine introduction and another starting in 2021 and also a no vaccination scenario. The vaccination scenarios reflect the programmatic context in the countries such as administration of hepatitis B immunoglobulin to infants born to HBsAg positive mothers and hepatitis B sero-prevalence among vaccinated cohorts of children. In the optimal scenarios, we assumed 95% coverage for all these interventions. We used two types of analysis: a birth cohort analysis tracking each cohort until death and a calendar-based analysis assessing the HBV burden annually from the year of vaccine introduction in each country up to 2040. Additionally, we estimated cost savings by calculating the avoided treatment costs and the costs associated with time spent in different health states, based on the outcomes of the calendar-based analysis. Our findings suggest that the existing vaccination programs have reduced HBV-related mortality in birth cohorts by 96.9 to 98.85%. The calendar-based analysis showed that vaccination programs have averted 24.08% (95% CI: 21.73–26.43%) of HBV-related deaths since their introduction, with the confidence interval reflecting variation in outcomes across the countries. Furthermore, high vaccination coverage resulted in a saving between US 6.07 million and US 34.8 million in treatment costs in the countries. This study underscores the importance of timely vaccination strategies as a powerful preventive measure in combating HBV globally.